Flora y vegetación del valle superior del Rió Atuel (Mendoza-Argentina) Flora and vegetation of the Upper Valley of the Atuel River (Mendoza-Argentina) - Ernesto A Morici; Anibal Prina; Graciela L Alfonso; Walter Muiño (Boletín de la Sociedad Argentina de Botánica, 2010)
El valle superior del Río Atuel presenta variaciones altitudinales y topográficas, siendo un territorio de confluencia de elementos propios de las provincias fitogeográficas Andina, del Monte, de la estepa Patagónica y de la Payunia. En este trabajo se estudia su flora y vegetación, a través de censos florísticos siguiendo la metodología de Braun-Blanquet (1979). A partir de la matriz de especies por censos se determinó el espectro biológico ponderado y la diversidad florística. Además, se estimó la cobertura basal registrándose los porcentajes de vegetación, broza, suelo desnudo, roca y fragmentos de roca. El estudio se desarrolló en un área restringida a la vertiente norte del Río Atuel entre su intersección con la Ruta Nacional 40 y las inmediaciones de la Planta de Azufre. En los censos se registraron un total de 89 especies pertenecientes a 36 familias, siendo las más numerosas Asteraceae, Poaceae, Verbenaceae, Fabaceae y Solanaceae. El 96% de las especies son nativas y sólo el 4% exóticas. Se diferenciaron 15 comunidades: 12 matorrales, 1 pastizal, 1 herbazal y 1 estepa de cojines. In this study we present a description of the flora and vegetation of the upper valley of Rio Atuel, Mendoza Province. In this area, characteristic taxa fron the Andina, Monte, Payunia and Patagonia Phytogeographical Provinces overlap their ranges. Considering that Atuel river high valley shows relevant altitudinal and topographical variations and a confluence of typical components from Andina, Monte, Patagonia and Payunia phytogeographic provinces, we plained to study, flora and vegetation. Floristic censuses were performed according to Braun-Blanquet (1979) and the matrix at coverage species was used to obtain cover data, weighted biological spectrum and floristic diversity. Furthermore, basal cover was estimated and vegetation, litter, bare soil, stones and stone pieces were recorded. This research was developed in an area restricted to the northern slope of Atuel river from its junction with National Route 40 (1800 m. a. s. l. ) to the surroundings of Planta de Azufre (2300 m. a. s. l. ) Asteraceae, Poaceae, Verbenaceae, Fabaceae and Solanaceae were the better representative plant families from a total of 89 species belonging to 36 families. 96 % of the species are native and 4 % are exotic. Fifteen communities were decribed: 12 shrubland, 1 grass, 1 herb community and 1 cushion steppe.